2021
DOI: 10.1155/2021/9941577
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Reduced Graphene Oxide

Abstract: The increasing biological use of graphene-based materials has prompted research inquiries on their effects on microorganisms. The work herein reported different types of microbiological activity of reduced graphene oxide (RGO). At relatively high concentrations (200 and 400 μg/mL), RGO exhibited antibacterial activity on the model bacterium Escherichia coli, while at lower concentrations (10 and 50 μg/mL), interestingly, no antibacterial effect was observed. Instead, an increase in the viable population after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Gram-positive strains MRSA, S. aureus , and B. subtilis showed susceptibility to HRG with a zone of inhibition of (28.7 ± 2.21, 24.31 ± 1.98 & 24.12 ± 1.17) in comparison to ampicillin with a zone of inhibition of (21.0 ± 2.27, 19.21 ± 1.82 & 18.86 ± 1.21), respectively ( p ≤ 0.05). A previous study found that E. coli showed resistance to reduced graph oxide nanoparticles, although it was susceptible to a high concentration of these nanoparticles ( Mann et al, 2021 ). Graphene and its derivatives also show a valuable impact in tissue engineering and exhibit strict antimicrobial activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-positive strains MRSA, S. aureus , and B. subtilis showed susceptibility to HRG with a zone of inhibition of (28.7 ± 2.21, 24.31 ± 1.98 & 24.12 ± 1.17) in comparison to ampicillin with a zone of inhibition of (21.0 ± 2.27, 19.21 ± 1.82 & 18.86 ± 1.21), respectively ( p ≤ 0.05). A previous study found that E. coli showed resistance to reduced graph oxide nanoparticles, although it was susceptible to a high concentration of these nanoparticles ( Mann et al, 2021 ). Graphene and its derivatives also show a valuable impact in tissue engineering and exhibit strict antimicrobial activities.…”
Section: Resultsmentioning
confidence: 99%
“…27, 19.21 ± 1.82 & 18.86 ± 1.21), respectively (p ≤ 0.05). A previous study found that E. coli showed resistance to reduced graph oxide nanoparticles, although it was susceptible to a high concentration of these nanoparticles (Mann et al, 2021). Graphene and its derivatives also show a valuable impact in tissue engineering and exhibit strict antimicrobial activities.…”
Section: Antibacterial Analysis Of Hrgmentioning
confidence: 99%
“…The antibacterial activity of the scaffold against E. coli plateaued while it exhibited a decrease in the behavior against S. aureus reaching 8.5±0.5 mm. This could be because at lower doses (10 and 50 g/mL), GO has been demonstrated to have no antibacterial action against E. coli bacteria [57] . However, GO demonstrated antibacterial action against E. coli bacteria at greater doses (200 and 400 g/mL) [57] .…”
Section: Resultsmentioning
confidence: 99%
“…This could be because at lower doses (10 and 50 g/mL), GO has been demonstrated to have no antibacterial action against E. coli bacteria [57] . However, GO demonstrated antibacterial action against E. coli bacteria at greater doses (200 and 400 g/mL) [57] . It is yet unknown how GO works against bacteria [58] .…”
Section: Resultsmentioning
confidence: 99%
“…Zn-HAp and Ti-HAp are more effective against each of the four bacteria, but HAp-rGO is more effective at greater doses. [68,69]. This might treat post-workplace injury disorders and bone joint infections at an early stage without identifying the major driver of the relevant microbe, allowing for a number of advancements in current clinical medicine [66,70].…”
Section: Antibacterial Activitymentioning
confidence: 99%